Optimal Design Of Stand Alone Hybrid PV / WTGS / Battery for Health Center Electricity System in Timor Leste - Alfredo Gusmao; Imam Robandi; Soedibyo Soedibyo (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
The use of renewable energy sources as a power plant has become an alternative option to provide electrical energy sources in a health center in Timor Leste. In this study a standalone hybrid generator system design consisting of Photovoltaic (PV), Wind turbine generation system (WTGS) and battery as energy storage will be made. The PSO algorithm is used to design optimal generator and battery capacity to obtain economic value. Optimal results are obtained by taking into account the potential of wind and solar energy and loads. The application of hybrid generating systems with renewable energy sources has several problems that must be resolved. The energy generated by renewable energy power plants is intermittent. Then this system requires energy storage to achieve power balance. The simulation results in this study show how to get the optimal value by using PSO algoritm, to reach power balance with the optimal and economical design of generator and battery capacity. Keywords: Hybrid; PV; WTGS; Battery; Control, Optimal Sizing, PSO